Study of process water recirculation in a flotation plant by means of process simulation - Michaux, Bruno; Hannula, Juho; Rudolph, Martin; Reuter, Markus A. (Minerals engineering, 2020)
•The flotation plant performance can be simulated with respect to water quality.•The impact of process water recirculation was studied using a simulation platform.•Water-saving strategies can be investigated using the simulation-based approach. One of the biggest challenges in the mining industry is the need for water management systems that consider production-related issues when the quality of process water is subject to variations. Part of the work required to tackle this challenge is the development of simulation platforms that correlate the quality of the process water to the processing plant performance. In this paper, the application of a previously developed method to include the impact of process water chemistry in the simulation of a flotation plant performance is presented. The water chemistry-dependent plant simulation is then used to investigate the impact of intensified process water recirculation on the flotation plant performance, thus showing the relevance of the previously developed approach to help implementing water-saving strategies in the mineral processing industry.